Unveiling the Untapped Potential: West Kalimantan's Competitiveness in the Era of the Industrial Revolution 4.0 Through Public Information Disclosure from a Political Perspective - Zhan, Fuzy Firda; Apriyandi, Dimas; Wahyudin, Eri (Journal of Social and Policy Issues, 2023)
The openness of public information in the form of easy access for the public is one of the pillars in realizing good governance in order to increase the nation's competitiveness towards a Superior Indonesia 2045. However, unfortunately, there are still several problems related to openness of public information such as limited access to public information, limited technology and infrastructure, lack of public awareness and education, and so on, shows that there is still a great need for attention from all parties regarding strengthening this to support West Kalimantan's competitiveness in the era of industrial revolution 4.0. This research was conducted with the aim of analyzing the potential competitiveness of West Kalimantan in the era of industrial revolution 4.0 through openness of public information from a political perspective. This research was conducted using a qualitative descriptive method with data sourced from literature studies and interviews. The results and conclusions of this research found that there are three potential competitive advantages for West Kalimantan in the Industrial Revolution 4.0 era through openness of public information from a political perspective, namely public awareness to obtain the right to open public information; government information media innovation towards Smart Province; and the role of youth through One Data West Kalimantan. As a recommendation, it is necessary to strengthen existing potentials continuously and synergistically between government, non-government and society so that West Kalimantan becomes more competitive in the era of Industrial Revolution 4.0 through openness of public information.